“If you show them respect, you’re going to [get] respect back": a theory for engaging First Nations for knowledge translation within a national nutrition and health survey - Wong, Jolian; Delormier, Treena W.; Bergeron, Dave; Chan, Hing M.; Gabriel-Ferland, Pamela; Jock, Brittany W. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Knowledge translation (KT) research aims to bridge the gap between research results and application which is vital to addressing health inequities. Despite the increasing emphasis on engaging Indigenous communities in research, there is limited research examining how to effectively engage communities to achieve Indigenous KT. The Food, Environment, Health, and Nutrition of First Nations Children and Youth (FEHNCY) is a nationally representative survey collaborating with First Nations’ (FNs) communities across Canada to inform policies and programs. The FEHNCY Community Engagement and Mobilization (CEM) supports partnerships with participating FNs communities and the application of study findings into action. This formative research aimed to examine how, for whom, and in which circumstances community engagement approaches support KT within FNs communities. Methods Data were generated with one rural and one semi-urban community participating in the FEHNCY pilot from the Atlantic and Eastern regions of Canada, respectively. A total of 26 in-depth interviews were conducted, 1 modified Talking Circle with community partners and 2 focus group discussions with the FEHNCY team. We used a realist approach combining inductive and deductive coding stages to develop a middle-range theory examining the connections between community engagement and KT. Results Our findings highlight the contexts, interventions, mechanisms, and outcomes that create pathways to KT. The participants described the societal, study and community contexts that affected engagement processes. The essential community engagement strategies included supporting Indigenous leadership in the research, supporting community decision-making, promoting project visibility, applying youth-specific engagement strategies, and incorporating FNs knowledges. The participants also described that centering positive relationships between research and community partners and valuing FNs knowledge systems were essential mechanisms for supporting KT. Lastly, participants highlighted KT outcomes namely, community self-determination in research, improved research findings and application of results for FNs benefit. Conclusion This research can inform the strategic use of community engagement in research for KT among FNs. This study is the first to generate a middle-range theory using primary data collection for supporting KT through community engagement approaches in Indigenous health research.